Clearance In Vivo of Instilled [H]Cholesterol from the Rat Lung - Michael A. Wyder; Shannon M. Griffin; D. Nicole Worsham; Edna S. Kaneshiro (Biochemistry Research International)
Phospholipids and lung surfactant proteins are known to be recycled within the lung alveolus mainly by uptake into type II epithelial cells that secrete lipid-enriched lung surfactant. Dipalmitoyl phosphatidylcholine (DPPC) is the major component of lung surfactant lipids and cholesterol is the second most abundant. However, cholesterol turnover in vivo has not been measured and it is not known how long steroidal compounds persist in the lung in intact animals. Here we report on experiments in which radiolabeled cholesterol was instilled into the lungs of rats, then at various postinstillation periods, radioactive sterols in lavage fluid, and in postlavage whole lungs were measured in individual animals. Radioactive sterols in the lungs remained high for a week and were still detectable 46 days later. The clearance rate during the initial postinstillation week was approximately 10% per day. Both radioactive free and esterified sterols were recovered from bronchoalveolar lavage fluid and postlavage lungs.